Nonoperative management of spontaneous epidural hematoma in hemophilia A - Thora, Ankit; Bhatnagar, Nishit; Tiwari, Anurag; Lingaiah, Purushotham; Rustagi, Nitesh (International Journal of Research in Orthopaedics, 2017)
Background: Spontaneous epidural haematoma is a rare clinical presentation and may be associated with coagulation disorders. These hematomas present usually with rapidly developing paraparesis and any delay in diagnosis may be disastrous. Methods: We included five patients of spontaneous epidural hematomas in hemophilia A with neurological deficit. They were treated non-operatively with factor VIII replacement therapy with oral tranexamic acid and intravenous dexamethasone as per protocol. All patients were followed up for 6 months and assessed for signs of neurological recovery and radiological resolution of hematoma. Results: All patients had complete motor recovery within 3 months of initiating treatment and showed resolution of hematoma on MRI. Conclusions: Prognosis following early initiation of correction of factor deficiency is good.